An Investigation of Mathematics Textbooks and their Use in English, French and German Classrooms: Who gets an opportunity to learn what? - Haggarty, Linda; Pepin, Birgit (British Educational Research Journal, 2002)
The article examines mathematics textbooks and their use in lower secondary classrooms in England, France and Germany. In particular, it looks at popular selling textbooks in each country and their treatment of ‘angle’, and examines teachers' mediation of those books based on observation and interview of a small sample of teachers in those countries. An analysis of the data suggests that learners in the different countries are offered different mathematics and given different opportunities to learn that mathematics, both of which are influenced by textbook and teacher. In addition, it identifies pupil access to textbooks in England as a cause for concern. It is argued that mathematics classroom cultures need to be understood in terms of a wider cultural and systemic context, in order for shared understandings, principles and meanings to be established.